Analyzing Written Communication Skills in Pre-service Science Teachers: A Gender Perspective - Budiarso, Aris Singgih; Supeno, Supeno; Mahardika, I Ketut; Wahono, Bevo; Wulandari, Ana Yuniasti Retno (FKIP Universitas Lampung, 2024)
This study explores the characteristics of Written Communication Skills (WCS) of pre-service science teachers from a gender perspective. WCS is a skill related to the ability to convey ideas in writing so that they can express their ideas, information, and arguments. WCS is important for pre-service science teachers to succeed in their studies and the workplace, especially when they teach in the classroom. This research is based on the differences in communication characteristics of female and male pre-service science teachers that have the potential to influence the way they write on the blackboard media. However, until now, references related to the characteristics of WCS, especially pre-service science teachers and their gender roles, have not been explored. To explore in depth the WCS of both gender groups with more flexibility, explorative is the method used in this study. This study involved 101 pre-service science teachers from three universities with similar regional characteristics. The data collection methods used included written tests. Exploratory results illustrate that pre-service science teachers covering the components of organization, development, expression, and content are at moderate and very good WCS levels. Mann-Whitney analysis showed that gender had no significant effect on WCS. However, the mean review illustrates that in the organization and development components, the mean of female is higher than male. In contrast, male have a higher mean than female in the expression and content components. Thus, there is no need for special treatment by considering gender differences when honing WCS. To increase the level of WCS of pre-service science teachers, educators in universities are seen as only needing to provide opportunities for pre-service science teachers to carry out problem formulation and self-group reflection. Keywords: pre-service science teachers, written communication skills, and gender roles. DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1397-1409